ANALISIS FAKTOR PEMBENTUK PERSEPSI NILAI DALAM MENINGKATKAN KEPUASAN PELANGGAN - Murhadi, Werner R. (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2004)
Tourism has a bright future and so does the hotel industry. Many opportunities in tourism sector have influenced the great number of tourism services provider and the effect is high competition. Increasing in competition can induce service quality of the corporation for creating the customer satisfaction. Customer satisfaction is influenced by many factors such as perceived valued by the customer. Perceived value is the consumer's overall assessment of the utility of a product based on perceptions of what received and what is given. Perceived Quality, Perceived Risk, Perceived Price and Price Fairness influence perceived value. Perceived price is formed by actual price that corporation charges to the consumer and brand class of product. This paper according to tourism sector, but the model can be used for others sector